2015
DOI: 10.1186/s40425-015-0091-z
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral imaging of formalin-fixed tissue predicts ability to generate tumor-infiltrating lymphocytes from melanoma

Abstract: BackgroundAdoptive T cell therapy (ACT) has shown great promise in melanoma, with over 50 % response rate in patients where autologous tumor-reactive tumor-infiltrating lymphocytes (TIL) can be cultured and expanded. A major limitation of ACT is the inability to generate or expand autologous tumor-reactive TIL in 25–45 % of patients tested. Methods that successfully identify tumors that are not suitable for TIL generation by standard methods would eliminate the costs of fruitless expansion and enable these pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 42 publications
1
99
0
3
Order By: Relevance
“…This might be of great impact, as high PD-L1 expression levels can be mediated by external stimuli, including cytokines secreted from immune cells, or intrinsic constitutive expression due to gene amplification (43), utilization of an ectopic promoter by translocation (44), disruption of the 3′ untranslated region of PD-L1 (45), or aberrant signaling pathways (46). Based on our previous data in melanoma (32), we investigated the ratios as well as the spatial relationship between CD8 + T cells and immune suppressors. Adapted from an optimal separation of a test cohort of 34 patients (Figure 6), FoxP3 and PD-L1 expression was analyzed within a 3-lymphocyte-wide distance (30 μm) around CD8 T cells; the numbers of FoxP3 + and PD-L1 + cells were normalized to the total number of CD8 T cells, and this number was equal to the SI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might be of great impact, as high PD-L1 expression levels can be mediated by external stimuli, including cytokines secreted from immune cells, or intrinsic constitutive expression due to gene amplification (43), utilization of an ectopic promoter by translocation (44), disruption of the 3′ untranslated region of PD-L1 (45), or aberrant signaling pathways (46). Based on our previous data in melanoma (32), we investigated the ratios as well as the spatial relationship between CD8 + T cells and immune suppressors. Adapted from an optimal separation of a test cohort of 34 patients (Figure 6), FoxP3 and PD-L1 expression was analyzed within a 3-lymphocyte-wide distance (30 μm) around CD8 T cells; the numbers of FoxP3 + and PD-L1 + cells were normalized to the total number of CD8 T cells, and this number was equal to the SI.…”
Section: Discussionmentioning
confidence: 99%
“…Multispectral imaging was performed as previously described in detail in the supplemental section of Feng et al (32) with minor changes, using mAbs directed against PD-L1 (E1L3N, Cell Signaling), CD8 (M239, Spring Bioscience), FoxP3 (236A/E7, Abcam), CD3 (2GV6, Ventana, prediluted, incubation for 45 minutes), CD163 (MRQ26, Ventana), and cytokeratin (AE1/AE3, DAKO, 1:100 dilution, incubation for 45 minutes) as well as DAPI (Invitrogen). TSACy5 (PerkinElmer Inc.), TSA-Cy3 (PerkinElmer Inc.), TSA-FITC (PerkinElmer Inc.), TSA-Alexa594 (Life Technologies), TSA-Biotin-Alexa514 (PerkinElmer Inc., Life Technologies), and TSA-Coumarin (PerkinElmer Inc.) were applied to each antibody.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the work has been done on human tissues as the staining of various epitopes on FFPE tissues has been optimized (4,22). For murine studies, characterization of the immune distribution in the tissue by IHC is lacking because many epitopes, notably CD4 and CD8, are sensitive to cross-linking and are unable to be detected in FFPE samples.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work showed that a TSA-based multiplex fluorescent imaging platform can be used to predict the success of culturing tumor-infiltrating lymphocytes from human melanoma samples (22). A simple diagram of this protocol is shown in Supplemental Fig.…”
Section: Murine Multiplex Fluorescent Ihcmentioning
confidence: 99%